2016
DOI: 10.4049/jimmunol.1600678
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Microenvironments in the Nasal Epithelium of Rainbow Trout (Oncorhynchus mykiss) Define Two Distinct CD8α+ Cell Populations and Establish Regional Immunity

Abstract: Mucosal surfaces require balancing different physiological roles and immune functions. In order to effectively achieve multifunctionality, mucosal epithelia have evolved unique microenvironments that create unique regional immune responses without impairing other normal physiological functions. Whereas examples of regional immunity are known in other mucosal epithelia, to date, no immune microenvironments have been described in the nasal mucosa, a site where the complex functions of olfaction and immunity need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 75 publications
1
26
0
Order By: Relevance
“…These results were consistent regardless of the source of cells used (HKLs, SLs or GLs) in vitro even when we pre-activated leucocytes were used. We have previously shown that HK and gut CD8α + cells express CCR7 (29) indicating that the source of cells used in our studies should not be reason why chemotaxis results were negative. Some reports have shown the importance of PGE2 on the migratory ability of CCL19 in mammalian monocytes (8386).…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…These results were consistent regardless of the source of cells used (HKLs, SLs or GLs) in vitro even when we pre-activated leucocytes were used. We have previously shown that HK and gut CD8α + cells express CCR7 (29) indicating that the source of cells used in our studies should not be reason why chemotaxis results were negative. Some reports have shown the importance of PGE2 on the migratory ability of CCL19 in mammalian monocytes (8386).…”
Section: Discussionmentioning
confidence: 90%
“…Leucocyte recruitment is easily visualized by histological examination due to the presence of an enlarged LP in the olfactory lamellae of vaccinated animals compared to controls (27). Furthermore, we have shown in the past that nasal delivery of IHNV vaccine results in MHC-II + responses in the OO of trout (29). Since in vitro Transwell assays may not mimic in vivo immune responses, we delivered rCK12a I.N.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations